Buffalo dreamer - Duncan, Violet (Nancy Paulsen Books, 2024)
When twelve-year-old Summer visits her family on a reservation in Alberta, Canada, she begins experiencing vivid dreams of running away from a residential school like the one her grandfather attended as a child and learns about unmarked children's graves, prompting her to seek answers about her community's painful past.